2001
DOI: 10.1103/physrevd.63.041503
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metric fluctuations and Hawking radiation

Abstract: In this Letter we study the gravitational interactions between outgoing configurations giving rise to Hawking radiation and in-falling configurations. When the latter are in their ground state, the near horizon interactions lead to collective effects which express themselves as metric fluctuations and which induce dissipation, as in Brownian motion. This dissipation prevents the appearance of trans-Planckian frequencies and leads to a description of Hawking radiation which is very similar to that obtained from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 18 publications
4
92
0
Order By: Relevance
“…The radiative corrections associated with these interactions in the free fall vacuum outside the black hole were studied in Ref. [17,18]. Beyond the local effects that would also be present in the vacuum of flat spacetime, it was found that there are further contributions, dominated by in-modes with Killing frequency ω in ∼ κ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiative corrections associated with these interactions in the free fall vacuum outside the black hole were studied in Ref. [17,18]. Beyond the local effects that would also be present in the vacuum of flat spacetime, it was found that there are further contributions, dominated by in-modes with Killing frequency ω in ∼ κ.…”
Section: Discussionmentioning
confidence: 99%
“…This would provide a different resolution to the species problem mentioned above (unless the number of species were of order M p /κ v ). On the other hand, as argued in [17,18], it is also possible that the cutoff arises from quantum gravitational effects in the black hole background, and that its value equals the Planck mass when measured in the static frame. 3 Such a cutoff would appear as Λ ∼ M 2 p /κ v in the freefall frame, and the regulated entropy would be of order A/L 2 p after all.…”
Section: Introductionmentioning
confidence: 99%
“…The gravitational back reaction also raises questions on the applicability of the semiclassical theory of gravity. Within this perspective, models were formulated [22,23] with the aim of studying the effects of fluctuations of the black-hole horizon on the Hawking radiation spectrum. In the absence of knowledge of the precise nature of the metric fluctuations near the horizon, the assumptions made here are that they can be treated classically and their effects on the propagation of quantum fields can be described via random differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the positive energy condition for the quintessence background, represented by the relation (16), it is required to have N q (u) 0. The radiation density is given by…”
Section: Black Hole-radiation Background Field Interactionsmentioning
confidence: 99%
“…Afterwards, some models to describe the classical essence of this radiation in a language which is free from the usual quantum field theoretic tools and is more familiar to the astrophysicists and relativists, have been introduced. For instance, the Vaidya solution [8][9][10] has provided a simple classical model for the black hole radiation and has been vastly investigated in this regard [11][12][13][14][15][16][17], see also [18][19][20][21][22][23][24][25][26][27][28][29] for more studies. In fact, the Vaidya solution is one of the non-static solutions of the Einstein field equations and can be regarded as a generalization of the static Schwarzschild black hole solution.…”
Section: Introductionmentioning
confidence: 99%